Cortisol and Growth Hormone Secretion in Relation to Linear Growth: Patients with Still's Disease on Different Therapeutic Regimens. Issue 5722 (5th September 1970) - Sturge, R. A.; Beardwell, C.; Hartog, M.; Wright, D.; Ansell, B. M.
Abstract : Linear growth was studied in 20 children suffering from Still's disease on various treatment regimens, and their ability to secrete growth hormone and cortisol was investigated. Growth recovered on reducing daily corticosteroid therapy or on changing to an alternative regimen. Retardation of growth was not due to an absolute inability to secrete growth hormone. Basal plasma cortisol levels and the plasma cortisol response to hypoglycaemia were reduced in patients on daily steroid therapy, but patients on alternate-day prednisone did not differ significantly in this respect from those on non-steroid regimens. Those on alternate-day corticotrophin showed preservation of the circadian rhythm but a subnormal response to hypoglycaemia.